Implementing training - Reay, David G. (Competent trainer's toolkit series, 1994)
This text provides the business manager or industrial trainer with guidelines on the implementation of successful training programmes using a variety of training methods. Separate chapters consider the most effective use of group training, side-by-side coaching, open learning, multimedia and much more. Making ample use of activities, exercises and questionnaires, the book examines a number of issues involved in the training process, including assessment.